Burden and quality of life of caregivers of chronic haemodialysis patients in Heraklion,Crete - Εrgini Antonaki; Dimitrios Xidakis; Μaria Kalogeropoulou; Μanolis Linardakis (Ene, 2018)
Introduction: Compared to other chronic diseases, burden and quality of life of caregivers of hemodialysis patients has not been extensively studied. However, it is of great interest because of the extent of involvement of caregiverσ in multiple levels of care (treatment, diet, hospitalization etc.). Aim: The aim of this study was to describe the characteristics of caregivers of chronic haemodialysis patients, and to assess their perceived burden and health-related quality of life. Additionally, the purpose of this study was to examine diverse factors influencing those two parameters. Methods: The sample of the study included 133 End Stage Renal Disease (ESRD) patients' caregivers from three dialysis units (2 public and 1 private) in the Prefecture of Heraklion Crete, Greece. Caregivers provided information on their socio-demographic characteristics and the clinical characteristics of the patients they were caring for. They also completed the "Health Survey Short Form Questionnaire 36/SF-36" and the "Zarit Burden Interview scale" (ZBIs) to assess the perceived burden. Results: Most caregivers were female (55,6%, n=74), aged >65 years (47%, n=62) and spouses of the patients. The mean score of total burden experienced was 42,4 (±21,6). The variables with the greatest impact on burden were personal strain and strain of the role. The most affected quality of life subscales were Emotional Role 34,9 (±40,3), General Health 42,3 (±22,8) and Physical Role 43,3 (±44,5), while the least affected was Physical Functioning 57,9 (±32,9). Linear regression analysis showed correlation of ZBIs with the Physical Component of SF-36 (R2=0,29, stand Beta=0,537, p<0,001) and the Mental Component of SF- 36 (R2=0,46, stand beta=0,683, p<0,001). Factors associated with perceived burden and/or health related quality of life were: caregiver's age, caregiver's educational level, distance from dialysis unit, residence in the same house with patient, caregiver's income, private or public dialysis unit and dialysis duration. Conclusions: The study highlighted that caregivers of hemodialysis patients exhibit moderate to severe burden and loss of quality of life. The re-design of a national health and social policy concerning end renal stage dialysis patients and their informal family caregivers, is imperative to be rated as a high priority issue.